2019
DOI: 10.1155/2019/9301382
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Progenitors and Organoids as a Prerequisite to Model Pancreatic Diseases and Cancer

Abstract: Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) are characterized by their unique capacity to stepwise differentiate towards any particular cell type in an adult organism. Pluripotent stem cells provide a beneficial platform to model hereditary diseases and even cancer development. While the incidence of pancreatic diseases such as diabetes and pancreatitis is increasing, the understanding of the underlying pathogenesis of particular diseases remains limited. Only a few recent publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…Additionally, organoids harboring Cdh1 loss and Kras mutation were transplanted back into nude mice, which induced the growth of tumors that represented poorly differentiated adenocarcinoma in contrast to mice transplanted with organoids containing either mutation alone. This highlights the versatility of organoids in their ability to be transplanted into mouse models to induce fibrosis and tumor formation, and other studies have also demonstrated success transplanting PDAC primary and metastatic murine organoids into nude mice [7,10]. Overall, these studies demonstrate the utility of murine-derived organoids to elucidate the role of molecular changes inherent in the progression from normal pancreatic tissues to PanIN to PDAC.…”
Section: Culture Of Mouse Pdac Organoidsmentioning
confidence: 63%
See 4 more Smart Citations
“…Additionally, organoids harboring Cdh1 loss and Kras mutation were transplanted back into nude mice, which induced the growth of tumors that represented poorly differentiated adenocarcinoma in contrast to mice transplanted with organoids containing either mutation alone. This highlights the versatility of organoids in their ability to be transplanted into mouse models to induce fibrosis and tumor formation, and other studies have also demonstrated success transplanting PDAC primary and metastatic murine organoids into nude mice [7,10]. Overall, these studies demonstrate the utility of murine-derived organoids to elucidate the role of molecular changes inherent in the progression from normal pancreatic tissues to PanIN to PDAC.…”
Section: Culture Of Mouse Pdac Organoidsmentioning
confidence: 63%
“…Pancreatitis is a condition characterized by inflammation and fibrosis. Patients with chronic pancreatitis have a significantly increased likelihood of developing pancreatic intraepithelial neoplasia (PanIN) and subsequently, PDAC [10]. The sequence of tumorigenesis from normal phenotype to malignancy has been shown in organoids derived from murine tissues.…”
Section: Culture Of Mouse Pdac Organoidsmentioning
confidence: 99%
See 3 more Smart Citations